2014
DOI: 10.1007/s10562-014-1421-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chemical Composition on the Catalytic Activity of Small Bimetallic FeRu Nanoparticles for Fischer–Tropsch Syntheses

Abstract: FeRu nanoparticles were prepared according to an organometallic route using {Fe[N(Si(CH 3) 3) 2 ] 2 } 2 and (g 4-1,5-cyclooctadiene)(g 6-1,3,5-cyclooctatriene) ruthenium(0) Ru(COD)(COT) precursors followed by their insertion into a mesoporous MCF-17 support host. The resulting nanoparticles had a uniform size of approximately 2 nm, with a relative Ru amount of up to 33 at.%. Steadystate Fischer-Tropsch catalysis at 6 bar total pressure (H 2 / CO = 1:1) demonstrated light olefins production with a selectivity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…In order to improve the activity of iron‐based catalysts, various metal promoters and alloys of iron with different metals have been studied. Particular attention has been paid to alloying iron with ruthenium owing to two main reasons: first, ruthenium is the most active FT metal, thus its addition is expected to increase conversion in iron‐based systems; second, alloying iron with ruthenium results in a change in the electronic d‐band structure that can give rise to distinct catalytic properties …”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the activity of iron‐based catalysts, various metal promoters and alloys of iron with different metals have been studied. Particular attention has been paid to alloying iron with ruthenium owing to two main reasons: first, ruthenium is the most active FT metal, thus its addition is expected to increase conversion in iron‐based systems; second, alloying iron with ruthenium results in a change in the electronic d‐band structure that can give rise to distinct catalytic properties …”
Section: Introductionmentioning
confidence: 99%
“…[1] Specific examples include the systems of Fe-Ru for efficient Fischer-Tropsch synthesis, [2] Al-Fe as aP d-free hydrogenation catalyst, [3] Rh-Pd for selectiveC Oo xidation, [4] and Pt-Co for renewable fuel generation [5] or the activation of Au in bimetallic systems. [6] Several studies have also demonstrated that bimetallic nanoparticles can outperform their monometallic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Several studies have also demonstrated that bimetallic nanoparticles can outperform their monometallic counterparts. [2][3][4][5][6][7] Specific intermetallic interactions in these alloyed or core-shell-type systemsw ere postulated to resulti ns ynergistic effects. This can include at uned electronic or geometric structure as well as an improved thermal or chemical stability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations